PENGARUH ANALISA TEKNIKAL TERHADAP HARGA SAHAMBANK BUMN DI BURSA EFEK INDONESIA TAHUN 2020 - Leri Santoso Hutasoit; Francis Hutabarat (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The development of capital market investment began to be loved by the public. This is because there is no nominal limit for investment. Investors can choose the capital and stock markets according to their wishes. This certainty is because it can profit if the investor decides the right trade. However, investors must also be observant in seeing the state of the company from certain capital markets. Because if you are careless, you can lose the funds you bought. This risk can be minimized by using technical analysis, namely by looking at the JCI, trading volume, and spread. Technical analysis is a technique used to analyze financial data from a company to find out the company's activities by looking at the price and volume. the effect of technical analysis on the stock price of state-owned banks on the Indonesia Stock Exchange (IDX) in 2020. The method for analyzing this research uses a descriptive and quantitative approach. The data used is secondary data from the stock exchange website. And what is used is daily data from 4 banks with 1 year observation so that the data obtained is 968 data. The analytical technique used is multiple regression analysis. The results of the research simultaneously that the JCI, trading volume, and spread variables can affect the IDX stock price in 2020. And by looking at the JCI, HS, and the existing volume, some investors can invest in the company.